2005
DOI: 10.1348/135910704x14582
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for controlled heroin use? Low levels of negative health and social outcomes among non‐treatment heroin users in Glasgow (Scotland)

Abstract: Drug research should more fully incorporate previously hidden populations to more fully inform theory and practice. The pharmacological properties of specific substances should not be assumed to inevitably lead to addictive and destructive patterns of drug use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 25 publications
1
52
1
Order By: Relevance
“…It may not be experienced as unproblematic by children however. The possibility of controlled heroin use is also precluded in this schema (Shewan andDalgarno, 2005, Warburton et al, 2005).…”
Section: The Drug/alcohol Divide: Embedding Risks In Substances and Fmentioning
confidence: 99%
See 1 more Smart Citation
“…It may not be experienced as unproblematic by children however. The possibility of controlled heroin use is also precluded in this schema (Shewan andDalgarno, 2005, Warburton et al, 2005).…”
Section: The Drug/alcohol Divide: Embedding Risks In Substances and Fmentioning
confidence: 99%
“…Drug problems tend to be defined in terms of use of the substance; there is great reluctance to accept that regular heroin use, for instance, is anything other than problematic, although the evidence is that it can be controlled given the right circumstances (Shewan andDalgarno, 2005, Warburton et al, 2005).…”
Section: The Drug/alcohol Divide: Embedding Risks In Substances and Fmentioning
confidence: 99%
“…Indeed, most people who currently use drugs or have used drugs in the past experience very few problems, either in terms of adverse health effects or brushes with authority. Although such statements generally relate to more 'recreational' drug use (Parker et al, 1998), a growing body of evidence shows that so-called 'harder' drugs can often be used in relatively un-problematic and controlled ways (Shewan and Dalgarno, 2005). In addition, research from a 'hidden' sample of drug users -that is those who have not been accessed via criminal-justice or treatment agencies -has demonstrated that heroin use is not always followed by criminal activity (Warburton et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Controlled and regulated use of heroin involve adhering to informal rules on the frequency of use of heroin, with whom it is taken and where it is used (Shewan & Dalgarno, 2006;Warburton, Turnbull, & Hough, 2005;Zinberg, 1984). Such opiate users are described as carrying out a tactical risk management that balances the pleasures of heroin use and the dangers of dependency.…”
mentioning
confidence: 99%